Analisis Hukum Terhadap Penerapan Hukum Tindak Pidana Pembantuan Dalam Tindak Pidana Korupsi Studi Kasus Putusan MA Nomor: 2166 K/Pid.Sus/2021 - Verawaty, Verawaty (Lex Librum : Jurnal Ilmu Hukum, 2024)
Corruption is an extraordinary crime that endangers all aspects of national life. Corruption often exploits assistance as a way for perpetrators to evade punishment. based on Supreme Court Decision Number 2166 K/Pid.Sus/2021. The criminal law aspect is the main subject of this research, particularly concerning the components of assistance, law enforcement, and the considerations judges take when making decisions. This research was conducted using a normative juridical approach that examines legislation, legal doctrine, and court decisions. The research results show that the laws used to assist in the corruption crime in this case meet the elements of assistance regulated in Article 56 of the Criminal Code. However, there are challenges in ensuring substantive justice, especially in considering the role and contribution of the accomplice to the main crime. The focus of this analysis is on the fulfilment of the elements of the crime of aiding, the role of the defendant in the overall corruption crime, and the conformity of the decision with the applicable laws and regulation.